IMPLEMENTASI SISTEM PENDEKATAN MANAJEMEN PENGAJARAN DAN PEMBELAJARAN - Awaluddin Sitorus (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
The system is a set of components or elements that interact with each other to achieve goals. In designing teaching and learning systems and educational and training procedures developed in industrial and military fields. The concept is the basis for identifying the objectives of a system. The purpose of a system can be natural and human. Education is more focused on the formation and development of personality. While training emphasizes the formation of education skills carried out in the school environment, while the use of training is generally based on the industrial environment. So, the principles of learning are instructions for teachers in implementing effective learning conditions. There are two characteristics of the teaching system approach, namely the system approach and the teaching and learning process to make it easy for students to learn.